The lncRNA RHPN1-AS1 downregulation promotes gefitinib resistance by targeting miR-299-3p/TNFSF12 pathway in NSCLC. Issue 14 (18th July 2018) - Li, Xuehao; Zhang, Xin; Yang, Chunlu; Cui, Su; Shen, Qiming; Xu, Shun
ABSTRACT: Although epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) gefitinib has exhibited notable clinical efficacy in non-small cell lung cancer (NSCLC) patients. However, its therapeutic efficacy is ultimately limited by the development of gefitinib resistance. The present study aimed to investigate the effects of the long non-coding RNA, RHPN1-AS1 on gefitinib resistance in NSCLC and explore the underlying mechanisms. In this study, RHPN1-AS1 was observed to be downregulated in gefitinib resistant patients and NSCLC cell lines. Besides, decreased expression of RHPN1-AS1 was found to be associated with poor prognosis of NSCLC patients. RHPN1-AS1 knockdown conferred gefitinib resistance to gefitinib sensitive NSCLC cells, whereas the overexpression of RHPN1-AS1 sensitized gefitinib resistant NSCLC cells to gefitinib treatment. Mechanistically, RHPN1-AS1 was found to positively regulate the expression of TNFSF12 by directly interacting with miR-299-3p. Collectively, RHPN1-AS1 modulates gefitinib resistance through miR-299-3p/TNFSF12 pathway in NSCLC. Our findings indicate that RHPN1-AS1 may serve as not only a prognostic biomarker for gefitinib resistance but also as a promising therapeutic biomarker and target for the treatment of NSCLC patients.